HPV vaccination in Africa in the COVID-19 era: a cross-sectional survey of healthcare providers’ knowledge, training, and recommendation practices - Fokom Domgue, Joel; Dille, Issimouha; Kapambwe, Sharon; Yu, Robert; Gnangnon, Freddy; Chinula, Lameck; Murenzi, Gad; Mbatani, Nomonde; Pande, Mala; Sidibe, Fatoumata; Kamgno, Joseph; Traore, Bangaly; et al. (Frontiers in Public Health, 2024)
Introduction Although the burden of cervical cancer in Africa is highest, HPV vaccination coverage remains alarmingly low in this region. Providers’ knowledge and recommendation are key drivers of HPV vaccination uptake. Yet, evidence about providers’ knowledge and recommendation practices about the HPV vaccine against a backdrop of emerging vaccine hesitancy fueled by the COVID-19 pandemic is lacking in Africa. Methods A cross-sectional study was conducted in 2021–2022 among healthcare providers involved in cervical cancer prevention activities in Africa. They were invited to report prior training, the availability of the HPV vaccine in their practice, whether they recommended the HPV vaccine, and, if not, the reasons for not recommending it. Their knowledge about the HPV vaccine was assessed through self-reporting (perceived knowledge) and with three pre-tested knowledge questions (measured knowledge). Results Of the 153 providers from 23 African countries who responded to the survey (mean age: 38.5 years, SD: 10.1), 75 (54.0%) were female and 97 (63.4%) were based In countries with national HPV immunization programs. Overall, 57 (43.8%) reported having received prior training on HPV vaccine education/counseling, and 40 (37.4%) indicated that the HPV vaccine was available at the facility where they work. Most respondents (109, 83.2%) reported recommending the HPV vaccine in their practice. Vaccine unavailability (57.1%), lack of effective communication tools and informational material (28.6%), and need for adequate training (28.6%) were the most commonly reported reasons for not recommending the HPV vaccine. While 63 providers (52.9%) reported that their knowledge about HPV vaccination was adequate for their practice, only 9.9% responded correctly to the 3 knowledge questions. Conclusion To increase HPV vaccination coverage and counter misinformation about this vaccine in Africa, adequate training of providers and culturally appropriate educational materials are needed to improve their knowledge of the HPV vaccine and to facilitate effective communication with their patients and the community.